Fugitive life : the queer politics of the prison state - Dillon, Stephen, 1983- (Book collections on Project MUSE., 2018)
During the 1970s in the United States, hundreds of feminist, queer, and antiracist activists were imprisoned or became fugitives as they fought the changing contours of U.S. imperialism, global capitalism, and a repressive racial state. In Fugitive Life Stephen Dillon examines these activists' communiqués, films, memoirs, prison writing, and poetry to highlight the centrality of gender and sexuality to a mode of racialized power called the neoliberal-carceral state. Drawing on writings by Angela Davis, the George Jackson Brigade, Assata Shakur, the Weather Underground, and others, Dillon shows how these activists were among the first to theorize and make visible the links between conservative "law and order" rhetoric, free market ideology, incarceration, sexism, and the continued legacies of slavery. Dillon theorizes these prisoners and fugitives as queer figures who occupied a unique position from which to highlight how neoliberalism depended upon racialized mass incarceration. In so doing, he articulates a vision of fugitive freedom in which the work of these activists becomes foundational to undoing the reign of the neoliberal-carceral state.